Biaya dan Tebal Perkerasan Kaku Menggunakan Metode MDP 2017 dan AASHTO 1993 - Rizal, Rikki Sofyan; Prihutomo, Nuzul Barkah; Raihan Wahyu Putra (Jurnal Poli-Teknologi, 2024)
The planning and evaluation process of toll road pavement thickness play a crucial role in sustainable toll road design. Road structure design needs to align with construction requirements, and pavement serves to shield the road layers from excessive pressure due to vehicle loads. Recalculating the rigid pavement thickness on the Cinere - Jagorawi toll road section III using the AASHTO and MDP methods aims to determine the most suitable method for determining toll road pavement thickness. Additionally, the study conducts cost calculations for rigid pavement work using slipform concrete paver and conventional methods. The research findings indicate that based on project data analysis, the pavement thickness using the AASHTO method is 16 cm, while the MDP method results in a thickness of 28 cm. The MDP analysis yields a pavement thickness identical to the field measurement of 28 cm, whereas the AASHTO method produces a pavement thickness 12 cm thinner than the field measurement. The effective cost of rigid pavement work using manual methods and concrete pavers amounts to Rp11,640,674,008.34. This cost applies to a thickness of 29 cm, a lane width of 3.7 m, and a work length of 5,700 m. The maximum work length is 3,291 m using manual methods, and the minimum work length is 2,409 m using concrete pavers.